Elastic Electron Scattering by Lead Atom in the Energy Range from 10 to 100 ev (Journal of Atomic and Molecular Sciences, 2012)
Electron scattering by lead atom is studied at energies 10, 20, 40, 60, 80 and 100 eV by applying a parameter-free complex optical potential. The real part of the complex optical potential includes the static potential $V_{st}(r),$ the polarization potential $V_{pol}(r)$ that consists of the short-range correlation and long-range polarization effects and $V_{ex}(r, k)$ term consisting of electron exchange interaction which is modeled by assuming the electron charge cloud as a free electron gas. The loss of flux into the inelastic channels is included via a phenomenological absorption potential. Our results are compared with the recent theoretical and experimental measurements.